Anatomic and neuromuscular characterisation of the equine cricothyroid muscle. (24th January 2013) - Reesink, H. L.; Hermanson, J. W.; Cheetham, J.; Mu, L.; Mitchell, L. M.; Soderholm, L. V.; Ducharme, N. G.
Summary Reasons for performing study As part of investigation into laryngeal stability and reanimation using functional electrical stimulation, the cricothyroid muscle might be utilised to increase laryngeal cross‐sectional area in horses with recurrent laryngeal neuropathy. For optimal electrode placement and muscle recruitment, the neuroanatomy and excitability of the equine cricothyroid muscle needs to be defined. Objectives To describe the anatomy, innervation and function of the equine cricothyroid muscle and its contribution to laryngeal diameter. Methods Seventeen equine larynges were collected at necropsy and 12 were grossly dissected. Seven larynges (five grade 1, two grade 4) were prepared for immunohistochemistry following gross dissection and 5 larynges were prepared for special staining: acetylcholinesterase staining of motor endplates (n = 3) and Sihler's staining (n = 2). Three larynges were stimulated following in situ cadaver dissection and 2 larynges were removed and stimulated ex vivo. Results Three neuromuscular compartments, each innervated by a primary nerve branch of the external branch of the cranial laryngeal nerve, were identified in all larynges. Stimulation of each neuromuscular compartment resulted in ventral displacement of the thyroid cartilage with respect to the cricoid cartilage, thereby increasing dorsoventral height of the rima glottis. Conclusions The equine cricothyroid muscle has 3 distinct neuromuscular compartments with discrete innervation, fibre type distribution and muscle fibre sizes. All neuromuscular compartments tense the vocal cords by increasing dorsoventral height of the rima glottis through ventral displacement of the thyroid cartilage with respect to the cricoid cartilage. Potential relevance Simultaneous functional electrical stimulation of the cricothyroid and dorsal cricoarytenoid muscles may enhance laryngeal cross‐sectional area in horses with recurrent laryngeal neuropathy.